On locally graded groups with minimality condition for a certain system of nonhypercentral subgroups - Artemovich, O. D. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We characterize groups without nontrivial perfect sections (in particular, solvable groups) with the minimality condition for the subgroups without hypercentral subgroups of finite index.